2008
DOI: 10.1007/bf03175578
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate on β-galactosidase production byKluyveromyces strains

Abstract: The aim of the present research was to investigate the influence of culture conditions on the levels of β-galactosidase (EC 3.2.1.23) activity produced by Kluyveromyces strains. Interest was focused on evaluating enzyme activity levels when lactose or cheese whey was employed as substrate in culture medium formulation. From an overall look at the obtained results, the tested strains were found to be able to produce β-galactosidase at promising levels. The use of cheese whey, either for strain maintenance and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
0
1
Order By: Relevance
“…Compositions of various media gave results contradicting with the comparative study carried out by Rollini et al [23]. Although Rollini et al [23] reported that the application of cheese whey as a carbon source will result in about 8-to10-fold increase in cell growth of K. lactis than lactose, our experimental results (Fig. 1) showed the opposite.…”
Section: Cultivations In Different Mediacontrasting
confidence: 91%
“…Compositions of various media gave results contradicting with the comparative study carried out by Rollini et al [23]. Although Rollini et al [23] reported that the application of cheese whey as a carbon source will result in about 8-to10-fold increase in cell growth of K. lactis than lactose, our experimental results (Fig. 1) showed the opposite.…”
Section: Cultivations In Different Mediacontrasting
confidence: 91%
“…The excellent tolerance of the K. marxianus PYCC 3286 strain to ethanol has been recently noted by other authors who showed that this strain can tolerate up to 79 g/L of ethanol [43]. Moreover, a high beta-galactosidase specific activity was also reported for this strain (3207 IU/g DW) [44]. It is conceivable that the combination of high ethanol tolerance and high beta-galactosidase activity are decisive features for the superior fermentative behavior displayed by the K. marxianus PYCC 3286 strain in the NF and RO retentates, both under mild and severe oxygen-limiting conditions.…”
Section: Resultssupporting
confidence: 55%